Creating common virtual ground: Protocols to democratize open VR research - Anand P. A. van Zelderen; Theodore C. Masters-Waage; Salvatore J. Affinito; Anely Bekbergenova; Kirsten Cowan; Tilo Hartmann; Mary M. Hausfeld; Albert Jolink; Jakob J. Korbel; Theo Lynn; Laetitia Renier; Dhruv P. Singh; et al. (Proceedings of the National Academy of Sciences, 2026)
By immersing participants in consistent virtual environments, VR enhances study realism, reduces confounding variables, and improves procedural control, offering a promising solution for scientists interested in studying behavior “in the wild.” The availability and documentation of data enabled by VR also help address replicability challenges. Despite vast potential, VR research is hindered by fragmentation, proprietary tools, and a lack of standardized practices, which limit its overall impact. This collaborative study presents an interactive checklist to support VR research from across disciplines to meet three essential protocols—interoperability, procedural standardization, and data sharing—that address these challenges by promoting open science and providing a common, easy-to-evaluate format for researchers to present projects to ethics boards, reviewers, and beyond. Together, these protocols can help VR research overcome replication barriers, democratize access to advanced tools, and establish VR as a robust method for rigorous, replicable scientific inquiry.